2015
DOI: 10.3390/cancers7040888
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Volumes and Prognosis in Laryngeal Cancer

Abstract: Tumor staging systems for laryngeal cancer (LC) have been developed to assist in estimating prognosis after treatment and comparing treatment results across institutions. While the laryngeal TNM system has been shown to have prognostic information, varying cure rates in the literature have suggested concern about the accuracy and effectiveness of the T-classification in particular. To test the hypothesis that tumor volumes are more useful than T classification, we conducted a retrospective review of 78 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 85 publications
0
28
0
1
Order By: Relevance
“…Only seven patients analyzed (12.3%) in their series had a laryngeal cancer, and no details were given on their outcomes. However, a significant association between the tumor volume and treatment outcome has been described in numerous studies and has been confirmed in laryngeal cancers for which the cartilaginous framework probably limits bulky tumor extension and a wide range of sizes . This is the main reason why we decided to focus on laryngeal cancers and to exclude hypopharyngeal neoplasms treated with a larynx preservation protocol.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Only seven patients analyzed (12.3%) in their series had a laryngeal cancer, and no details were given on their outcomes. However, a significant association between the tumor volume and treatment outcome has been described in numerous studies and has been confirmed in laryngeal cancers for which the cartilaginous framework probably limits bulky tumor extension and a wide range of sizes . This is the main reason why we decided to focus on laryngeal cancers and to exclude hypopharyngeal neoplasms treated with a larynx preservation protocol.…”
Section: Discussionmentioning
confidence: 92%
“…This is the main reason why we decided to focus on laryngeal cancers and to exclude hypopharyngeal neoplasms treated with a larynx preservation protocol. Interestingly, Issa et al in their series assessed that the relationship between the tumor volume and treatment outcomes was neutralized when the volume was considered after IC . This raises questions about the correlation between the response to IC and treatment outcomes in a homogeneous series of patients with laryngeal cancers.…”
Section: Discussionmentioning
confidence: 99%
“…These toxicities appear associated with larger initial tumor volumes and with radiation effects that are intensified by chemotherapy. Tumor volume has also been implicated as an important prognostic factor in chemoradiation treatment of advanced laryngeal cancer and less important in surgical management 40,41 . This has led to a re-emphasis on use of primary total laryngectomy with appropriate voice rehabilitation as a good treatment alternative, particularly in patients with extensive T4a cancers, since swallowing function after treatment is often better and frequently quality of life outcomes are similar to larynx preservation 15,42,43 .…”
Section: Discussionmentioning
confidence: 99%
“…The influence of induction chemotherapy on the significance of prognostic factors in laryngeal cancer has long been an issue of debate. For example, the initial tumor volume has been reported to correlate with survival, whereas the volume after chemotherapy does not appear to have prognostic value …”
Section: Discussionmentioning
confidence: 99%